Propriedades termodinâmicas de gelos de spin artificiais na rede de Penrose - João Vitor Nunes Santos (2023)
The geometric frustration in materials known as spin ices has awakened great interest among researchers in the last decade. These materials have magnetic moments that obey magnetic ice rule, a rule similar to the one that water molecules retain in the solid state. Studies in this area also involve lattices of magnetic nanoislands, known as artificial spin ices (ASI). These nanostructures are manufactured using electronic lithography, which allows precise control of its geometry and magnetic interactions. Unlike natural spin ices, ASI allow the direct observation of the systems microstate, allowing the identification of colective excitations such as magnetic monopoles and the investigation of their properties. In this work we are interested in the study a ASI in the Penrose tile and further analysis of system thermodynamic properties. Thermodynamic analysis will allow the understanding of the behavior of thermodynamic quantities such as energy, magnetization, specific heat and magnetic susceptibility. In addition, investigating the dependence of these quantities on the temperature and system parameters, provide a more complete view of its properties.